EKVATOR BÖLGESİNDE KIRILMA İNDİSİNİN ENLEMLE DEĞİŞİMİ - KURT, KADRİ (Fırat Üniveristesi, 2008)
Bu tezde, ekvator bölgesindeki iyonkürenin ordinari, kutuplanmış ve ekstraordinari dalgaların çarpışmasız ve çarpışmalı halleri için kırılma indisi çalışılmıştır. Hesaplamalar, 21 Mart, 21 Haziran, 23 Eylül, 21 Aralık günleri ile saat 1200 YZ ve 2400 YZ için yapılmıştır.Ordinari dalganın kırılma indisinin gündüz değerleri, tüm mevsimler için 40 K ile 160 K enlemleri arasında maksimum, gece değerleri ise 80 G ile 80 K enlemleri arasında minimum oluğu tesbit edilmiştir. Sola kutuplanmış dalganın kırılma indisinin değerleri tüm mevsimlerde gündüz, 40 K ile160 K enlemleri arasında maksimum, gece değerleri 00 ile 120 K enlemleri arsında, 21 Aralık için maksimum, diğer tüm mevsimler için minimumdur. Sağa kutuplanmış dalganın kırılma indisinin değerleri tüm mevsimlerde gündüz için, 100 K enleminde maksimum, gece değerleri 40K enleminde minimum olmaktadır. Ekstraordinari dalganın kırılma indisi, 21 Mart için gündüz 240K enleminde minimum iken gece maksimum olmaktadır. Bu kırılma indisinin 23 Eylül'de ise 120K enleminde hem çarpışmasız hem de çarpışmalı haller için maksimum olduğu görülmüştür. Ekstraordinari dalganın kırılma indisi çarpışmalı haller için 21 Aralık'ta, 40K enleminde maksimum, çarpışmasız haller için 220 K enleminde de minimum olduğu görülmüştür.Anahtar kelimeler: Ekvator anormalliği, Kırılma indisi, İyonküre

In this thesis, the refractive index has been studied for ordinary, the polarized and extraordinary waves for both collisional and non-collision conditions in the equatorial region of inosophere. The calculations have been done for 21 March, 21 June, 23 September and 21 December days for local times 1200 and 2400.The refractive index of ordinary wave has maximum between 40N-160N latitudes in daytime. It has been taking minimum values 80 N and 80 S latitudes for the whole of seasons by night. The refractive index of the left-handed polarized wave has been taking maximum values between 40N-160N latitudes by day for every season. The refractive index of the right-handed polarized wave has been taking maximum value at 100N latitude for all of season by day but it has minimum value at 40N latitude by night. While the refractive index of the extraordinary wave has been taking minimum at 240N latitude for 21 march daytime, it has becoming maximum for the same latitude nighttime. For same wave, the maximum values occur at 120N latitude for 23 September for both collisional and non-collision cases. The refractive index of the extraordinary wave has maximum at 40N latitude for December for collisional case but in the non-collision case, it becomes minimum at 220N latitude.Keywords: Equatorial Anomaly, Refractive Index, Ionosphere
The variations of the refractive index in the equatorial region with latitude
Keywords: Fizik ve Fizik Mühendisliği